PENGARUH DIVIDEN PAYOUT RATIO DAN EARNING VOLATILITY TERHADAP VOLATILITAS HARGA SAHAM - Indra Saputra; Mega Andani (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2022)
This research aims to determine and analyze the Dividend Payout Ratio and Earning Volatility of Stock Price Volatility in Manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The research method used is quantitative. The research population is 156 manufacturing companies. Sampling in this research using purposive sampling method total to 27 manufacturing companies. The results show that dividend payout has an effect on stock price volatility in manufacturing sector companies listed on the Indonesia Stock Exchange in 2018-2020. Earning Volatility (EV) has no effect on stock price volatility in manufacturing sector companies listed on the Indonesia Stock Exchange in 2018-2020. Dividend Payout and Earning Volatility have a simultaneous effect on Stock Price Volatility in manufacturing sector companies listed on the Indonesia Stock Exchange in 2018-2020.